From Suppurative Inflammation to Fibrotic Remodeling in Cutaneous Nocardiopsis Infection - Naixuan Lin; Keke Huang; Degang Yang (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. In the present case report, a cutaneous infection caused by the rare actinomycete Nocardiopsis sp. TSRI0078 is described. A 77-year-old woman with a medical history of hypertension and diabetes presented with ulcerated purplish-red nodules on the lower extremities that had persisted for 3 months. A histopathological examination revealed infectious granulomas predominantly composed of neutrophils. After empirical antibiotic therapy proved ineffective, the pathogen was confirmed to be Nocardiopsis sp. TSRI0078 via polymerase chain reaction testing, gene sequencing, and microbial culture. Subsequent treatment with oral trimethoprim–sulfamethoxazole led to gradual regression of the lesions and scar formation. With only 11 human infection cases reported globally, a clear understanding of the clinical manifestations of Nocardiopsis infections is lacking. This pathogen should be considered in the differential diagnosis of chronic, unexplained cutaneous lesions, particularly in patients with underlying diseases. A combination of molecular and conventional microbiological examinations facilitates early diagnosis, and trimethoprim–sulfamethoxazole may represent an effective therapeutic option.